Specifics of professional phagocyte activity in residents of radiation-contaminated areas - V. Sokolenko (Vìsnik: Kiïvsʹkij Nacìonalʹnij Unìversitet Imenì Tarasa Ševčenka. Bìologìâ, 2016)
We studied phagocytic activity indices in patients aged 18-24 who lived from birth in the territories contaminated with radionuclides due to the Chornobyl catastrophe. We revealed that in the analyzed years there has been a gradual decline in indices of phagocytic number and phagocytic index, especially pronounced for populations of monocytes. There is a growing negative correlation between the activity of 137Cs in contaminated areas and phagocytic activity of monocytes in the population of these territories from 1995 to 2014.